Sustaining Life on Planet Earth: Metalloenzymes Mastering Dioxygen and Other Chewy Gases - Kroneck, Peter M. H.; Sosa Torres, Martha E. (Metal Ions in Life Sciences,, 2015)
MILS-15 provides an up-to-date review of the metalloenzymes involved in the activation, production, and conversion of molecular oxygen as well as the functionalization of the chemically inert gases methane and ammonia. Found either in aerobes (humans, animals, plants, microorganisms) or in anaerobes (so-called "impossible bacteria") these enzymes employ preferentially iron and copper at their active sites, in order to conserve energy by redox-driven proton pumps, to convert methane to methanol, or ammonia to hydroxylamine or other compounds. When it comes to the light-driven production of molecular oxygen, the tetranuclear manganese cluster of photosystem II must be regarded as the key player. However, dioxygen can also be produced in the dark, by heme iron-dependent dismutation of oxyanions. Metalloenzymes Mastering Dioxygen and Other Chewy Gases is a vibrant research area based mainly on structural and microbial biology, inorganic biological chemistry, and environmental biochemistry. All this is covered in an authoritative manner in 7 stimulating chapters, written by 21 internationally recognized experts, and supported by nearly 1100 references, informative tables, and over 140 illustrations (many in color). MILS-15 provides excellent information for teaching; it is also closely related to MILS-14, The Metal-Driven Biogeochemistry of Gaseous Compounds in the Environment.  Peter M. H. Kroneck is a bioinorganic chemist who is exploring the role of transition metals in biology, with a focus on functional and structural aspects of microbial iron, copper, and molybdenum enzymes and their impact on the biogeochemical cycles of nitrogen and sulfur. Martha E. Sosa Torres is an inorganic chemist, with special interests in magnetic properties of newly synthesized transition metal complexes and their reactivity towards molecular oxygen, applying kinetic, electrochemical, and spectroscopic techniques.